The evolution of microstructure in annealed LaFeSi-type alloys - Gębara, Piotr; Pawlik, Piotr; Kulej, Edyta; Wysłocki, Jerzy J.; Pawlik, Katarzyna; Przybył, Anna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The evolution of microstructure and the phase constitution of the LaFe11.0Co0.8(Si0.4Al0.6)1.2 alloy in as-cast state and after subsequent annealing at 1323 K for 10, 20, 49 days was studied. In the LaFe11.0Co0.8(Si0.4 Al0.6)1.2 alloy after arc-melting, the dominant dendritic α-Fe phase crystallizes, which is confirmed by X-ray diffraction. Annealing of the samples resulted in evolution of microstructure and the phase constitution. Prolonged annealing of the samples causes almost full homogenization of the alloy with the single-phase structure identified as La(Fe0.85Co0.06Si0.04Al0.05)13 phase of the NaZn13-type structure.
Optica Applicata, Vol. 39, 2009, nr 4, s. 761-764
Keywords: optyka; microstructure; magnetocaloric materials; X-ray diffraction